2015
DOI: 10.1371/journal.pone.0135713
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, High-Sensitivity C-Reactive Protein and Mortality in Chinese with Coronary Artery Disease

Abstract: BackgroundTo investigate single and joint associations of body mass index (BMI) and serum high-sensitivity C-reactive protein (hsCRP) with death.MethodsThe study included 1871 coronary artery disease (CAD) patients aged 40–85 year-old recruited from 2008 to 2011. Cox regression models were used to estimate the association of BMI and hsCRP with mortality. The data was analyzed in 2014.ResultsDuring 3.1 years follow-up, 141 deaths were recorded, 110 died of cardiovascular disease (CVD). After adjustment of major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
1
19
1
1
Order By: Relevance
“…Although in several studies a positive relationship was observed between BMI status and hs-CRP levels, our findings were not significant [29][30][31][32][33]. Possible explanation for this strange result might be malnutrition-inflammation syndrome.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Although in several studies a positive relationship was observed between BMI status and hs-CRP levels, our findings were not significant [29][30][31][32][33]. Possible explanation for this strange result might be malnutrition-inflammation syndrome.…”
Section: Discussioncontrasting
confidence: 90%
“…Due to inflammation responses in the body, and especially in acute phase responses, anorexia and promotion of catabolic process stimulating protein degradation would occur, which consequently declining BMI levels and CVDs risks. Furthermore, nature of the inflammation creates defense against injurious stimuli, therefore, mild elevation in inflammatory biomarkers specifically hs-CRP, which are mostly observed in overweight persons, have another explanation [32]. Several longstanding comprehensive studies are necessary to investigate the exact associations of body weight with hs-CRP values in order to predict the CVDs likelihood.…”
Section: Discussionmentioning
confidence: 99%
“…This is reported in several cross‐sectional studies and meta‐analyses . Additionally, lost weight reduced C‐reactive protein (CRP) , and obesity‐related inflammation has been associated with increased risk of cardiovascular diseases (CVD), CVD‐mortality and overall mortality . Obesity stimulates production of a number of molecules including pro‐inflammatory metabolites (adipokines) in adipose tissue, and several of them are linked to overweight .…”
Section: Introductionmentioning
confidence: 98%
“…In our study the cut point was set at a BMI of 30 kg/m 2 , whereas in the third National Health and Nutrition Examination Survey the cut point was 25 kg/m 2 . Different results were seen in a Japanese study [23] that divided the cohort of 1,871 patients with coronary artery disease into three groups: BMI < 24 kg/m 2 , 24.0-27.9 kg/ m 2 and ≥ 28 kg/m 2 . Using the group with a BMI of 24.0-27.9 kg/m 2 and CRP < 3 mg/L as reference, the hazard ratio was 1.16 for the group with the same BMI but with CRP values of ≥ 3 mg/L.…”
Section: Discussionmentioning
confidence: 74%